Ḥeseḏ sebagai Permenungan Teologi Keringkihan dalam Perspektif Disabilitas Berdasarkan Narasi 2 Samuel 9:1-13 - Yahya Afandi (Sekolah Tinggi Teologi Intheos Surakarta, 2023)
Abstract. The determination to make the earth an inclusive place for all groups requires comprehension, awareness, and ongoing collaboration. One of the impediments to realizing this dream is the stigma and discrimination against various types of weakness, vulnerability, deficiencies, and limitations, such as the disabilities, both physical and mental, that most people around us experience. The locus text from 2 Samuel 9:1-13 will be reread and reinterpreted in light of Jeremy Schipper's analysis of the term ḥeseḏ in the narratives of King David and Mephibosheth, in order to gain a new understanding of vulnerability in the context of disability in theological discourse. The reading resulted the invitation for everyone to experience the incarnation event as an effort by which the Almighty embraces the vulnerable, thus providing an array for discussion about how weakness and vulnerability should be accepted and celebrated in equal social relations.Abstrak. Perjuangan mewujudkan bumi menjadi tempat yang inklusif bagi semua golongan menuntut pemahaman, kesadaran, dan usaha bersama secara terus-menerus. Salah satu penghalang terwujudnya mimpi tersebut adalah stigma dan diskriminasi terhadap berbagai jenis kelemahan, keringkihan, kekurangan serta keterbatasan, misalnya disabilitas baik fisik maupun mental yang dialami oleh kebanyakan orang di sekeliling kita. Analisis Jeremy Schipper terhadap terma ḥeseḏ dalam narasi Raja Daud dan Mefiboset, akan dijadikan lokus dan basis teks untuk membaca dan menafsirkan ulang teks 2 Samuel 9:1-13, demi menemukan pemahaman baru diskursus teologi keringkihan dalam perspektif disabilitas. Pembacaan tersebut menghasilkan ajakan bagi setiap orang untuk menghayati peristiwa inkarnasi, yang merupakan upaya Sang Maha Kuat merengkuh sang ringkih, sehingga menyediakan ruang percakapan bagaimana seharusnya kelemahan dan keringkihan diterima serta dirayakan dalam relasi sosial yang setara.